Conservation and Indigenous resistance: Protected Areas and extractive agendas in the Peruvian Amazon - Watson Jimenez, Ana (2022)
Expanding natural protected areas in the Peruvian Amazon compete with indigenous interests and resource extraction, in a dynamic process of endorsement and enforcement by local indigenous communities. The analysis presents a geographical case study of Peru’s emblematic Camisea gas extraction project in the Amazonian Lower Urubamba valley, Cusco. The focus is on two protected areas —Matsigenka Communal Reserve and Megantoni National Sanctuary— that were created alongside the gas project in the early 2000s, strategically supported by local indigenous communities. The study argues that the intersections of extractive and conservation agendas in Camisea have created ambiguous and novel spaces for the expression of local indigenous agendas, while neoliberal conservation territorial logics simultaneously limit them. This empirical analysis contributes to a deeper empirical understanding of Indigenous conservation priorities, political demands, and long-term strategies regarding territorial and legal categories of conservation, carefully negotiated within highly fragmented and weak formal institutional state arrangements in the Peruvian Amazon.